2016
DOI: 10.1016/j.molcatb.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro hydroxylation of cineole and camphor by cytochromes P450CYP101A1, CYP101B1 and N242A CYP176A1

Abstract: In vivo and In vitro hydroxylation of Cineole and Camphor by Cytochromes P450CYP101A1, CYP101B1 and N242A CYP176A1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…This observation, combined with the minimal shifts triggered by the camphor enantiomers, indicates that 1,8-cineole is the physiological substrate for the newly discovered P450s. Furthermore, despite being shown to oxidize 1,8-cineole, CYP101A has a K d value that is higher and a spin-state shift that is smaller (14) than those of the P450s from S. yanoikuyae. These functional variations due to sequence divergence and presumably structural differences warrant further investigations and comparison.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This observation, combined with the minimal shifts triggered by the camphor enantiomers, indicates that 1,8-cineole is the physiological substrate for the newly discovered P450s. Furthermore, despite being shown to oxidize 1,8-cineole, CYP101A has a K d value that is higher and a spin-state shift that is smaller (14) than those of the P450s from S. yanoikuyae. These functional variations due to sequence divergence and presumably structural differences warrant further investigations and comparison.…”
Section: Discussionmentioning
confidence: 90%
“…CYP101A1 was char-acterized based on its activity with camphor (18). More recently, both CYP101B1 and CYP101A1 also have been shown to hydroxylate 1,8-cineole, producing a range of hydroxy-1,8-cineole isomers (14). The P450 from C. braakii is unique, as no other bacterial enzymes have been found that belong to the CYP176 family or use similar electron transfer partners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that P450 enzymes can hydroxylate 1,8‐cineole . 1,8‐Cineole is a renewable compound found in eucalyptus oil that belongs to the diverse class of monoterpenoids .…”
Section: Introductionmentioning
confidence: 99%